2013
DOI: 10.1111/jawr.12070
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Modeling to Evaluate Water Management Scenarios in the Rio Grande Basin

Abstract: This article describes the collaborative modeling process and the resulting water resources planning model developed to evaluate water management scenarios in the transboundary Rio Grande basin. The Rio Grande is a severely water stressed basin that faces numerous management challenges as it crosses numerous jurisdictional boundaries. A collaborative process was undertaken to identify and model water management scenarios to improve water supply for stakeholders, the environment, and international obligations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…A number of recent case studies that highlight local water managers' identified strategies and barriers in adapting to climate-induced water supply variability compare well with our case study findings [29,31,36,45,[88][89][90]. In the Wasatch Range of northern Utah, for example, water managers described challenges with enhancing water supply to meet growing population demand, obtaining funds to build and restore aging infrastructure, and coordinating diverse water use interests [31].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A number of recent case studies that highlight local water managers' identified strategies and barriers in adapting to climate-induced water supply variability compare well with our case study findings [29,31,36,45,[88][89][90]. In the Wasatch Range of northern Utah, for example, water managers described challenges with enhancing water supply to meet growing population demand, obtaining funds to build and restore aging infrastructure, and coordinating diverse water use interests [31].…”
Section: Discussionsupporting
confidence: 77%
“…Thus, collaborative research that facilitates increased communication and coordination should inform future climate planning so that it meets the needs of diverse water users [90].…”
Section: Discussionmentioning
confidence: 99%
“…Efficient and effective water management requires collaboration among stakeholders to achieve common goals in allocating limited water resources [87]. There is a potential for the market to move toward integrated We find that for up to $154 million, including transaction costs, a maximum of 800 million m 3 (650,000 ac-ft) of water use could be avoided by implementing four best management practices for irrigation efficiency across Hidalgo and Cameron counties in South Texas.…”
Section: Opportunities For Collaboration: Irrigation and Hydraulic Frmentioning
confidence: 95%
“…Efficient and effective water management requires collaboration among stakeholders to achieve common goals in allocating limited water resources [87]. There is a potential for the market to move toward integrated partnerships that benefit irrigators or irrigation districts and oil and gas operators rather than existing adaptive strategies to combat water stress.…”
Section: Opportunities For Collaboration: Irrigation and Hydraulic Frmentioning
confidence: 99%
“…We included Sandoval‐Solis et al . () to represent “shared vision planning” as a collaborative modeling approach closely related to (but not always including) system dynamics (Cardwell and Langsdale, ; Mirchi et al ., ; Langsdale et al ., ; Palmer et al ., ; Rivera et al ., ; Collier et al ., ). Based on these criteria, 16 case studies were reviewed to derive evidence about key benefits and limits experienced by stakeholders and facilitators in the domain of water management.…”
Section: Introductionmentioning
confidence: 99%